Measurement and validation of a three factor hierarchical model of competitive anxiety - Jones, E. S.; Mullen, R.; Hardy, L. (Psychology of Sport and Exercise, 2019)
Objectives: A novel analytical framework was used to re-examine and extend Cheng, Hardy and Markland`s (2009) hierarchical model of anxiety. The modified model was characterized by six first order constructs, with worry, private self-focus and public self-focus representing cognitive anxiety, somatic tension and autonomous hyperactivity representing physiological anxiety and perceived control representing the regulatory dimension. It was hypothesized that these six first order constructs were formative indicators of the second order factors and this hypothesis was tested using Partial Least Squares analysis. Factor validity of the original hierarchical model proposed by Cheng et al. was investigated. Subsequently, items were refined, the hierarchical model extended, and factor and predictive validity investigated further. Method: Prospective data was collected from three samples (N = 174, 516, 43), and a series of factor analyses were conducted including Confirmatory Factor Analysis and Partial Least Squares modeling. Multivariate analysis examined the predictive validity of the model using a performance measure as the dependent variable. Results: The original model revealed a poor fit, with poor item loadings and discriminant validity. Subsequent analysis established a refined 25 item measure, which produced support for a fully differentiated hierarchical model of competitive anxiety. MANOVA revealed a significant effect for the control factor, with those achieving superior performance reporting significantly higher levels of perceived control. Conclusions: A fully differentiated hierarchical model was supported, which crucially depicts the first order factors of competitive anxiety that form the 3 s order dimensions. This provides a model that is a better fit with theory and provides a more refined diagnosis tool for applied sport psychologists.